PERAN ORANG TUA DALAM MENDUKUNG TUMBUH KEMBANG ANAK BERKEBUTUHAN KHUSUS (AUTISME ) DI SKH 01 KOTA CILEGON - Uun Unayah; Yahdinil Firda Nadhira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Autism is a comprehensive developmental disorder that results in obstacles in socialization, communication, and behavioral abilites. This research was conducted at skh 1 cilegon using qualitative methods, data collection methods using observation, interviews and documentation. The research subjects were parents, teachers, and 1 child with autism. The results of this research show that children with autism have difficulty communicating.